Asprellcosides B of Ilex asprella Inhibits Influenza A Virus Infection by Blocking the Hemagglutinin- Mediated Membrane Fusion - Zhang, Wen; Chen, Si-Tai; He, Qiu-Yan; Huang, Li-Quan; Li, Xiong; Lai, Xiao-Ping; Zhan, Shao-Feng; Huang, Hui-Ting; Liu, Xiao-Hong; Wu, Jianguo; Li, Geng (Frontiers in Microbiology, 2019)
Ilex asprella is routinely used in China as a traditional medicinal herb to treat influenza (Flu). However, its specific antiviral activity and underlying molecular mechanism have not yet been determined. In this study, we sought to determine the antiviral activity and mechanism of Asprellcosides B, an active component extracted from Ilex asprella, and used against the influenza A virus cell culture. We also performed a computer-assisted structural modeling analysis and carried out surface plasmon resonance (SPR) experiments in the hope of determining the viral target of Asprellcosides B. Results from our studies show that Asprellcosides B reduced virus replication by up to 63% with an IC50 of about 9 μM. It also decreased the low pH-induced and virus-mediated hemolysis by 71% in vitro. Molecular docking simulation analysis suggested a possible binding of Asprellcosides B to the hemagglutinin (HA), which was confirmed by a surface plasmon resonance (SPR) assay. Altogether, our findings demonstrate that Asprellcosides B inhibits the influenza A virus, through a specific binding to the HA, resulting in the blockade of the HA-mediated membrane fusion.